Preeclampsia Part 2: fisiopatologia e trattamento - Stefano Michelassi (AboutScience Srl, 2019)
Preeclampsia is a pregnancy-specific disorder usually defined as new-onset hypertension and proteinuria after the 20th week of gestation. Preeclampsia is a systemic disease with multiorgan involvement, and it is associated with a high risk of maternal and fetal morbidity and mortality. To date its pathogenesis is not completely understood, but placental hypoxia or hypoxia/reoxigenation may be the basic condition leading to systemic inflammation and endothelial dysfunction that induce all the clinical manifestations of the disorder. Delivery is the only curative treatment. Indeed, for the management of preeclampsia one needs to consider both the maternal risks due to continued pregnancy and the fetal risks associated with induced preterm delivery.